6x
x^2 + 6x + 9 cannot be simplified further. If x^2 + 6x + 9 = 0 then we can solve for x. x^2 + 6x + 9 can be broken into a binomial: (x+3)(x+3), which then gives us x = -3.
you multiply it
6x-4 = 18 6x = 18+4 6x = 22 x = 22/6 = 3 and 2/3
If 6x + 10 = 11x , then x=2.
6x-3x =6 3x=6 so 6 divided by 3 = 2
-4x-6x = -20 -10x = -20 Divide both sides by -10 rembering that a minus divided into a minus the result is positive: x = 2
you just add 6x+9x to get 15x then minus 25 from 18 to get -7 thus the answer will be 15x-7
-6x
To solve this equation, we will first subtract 2x from each side:8x=2x+6 (8x minus 2x=6x)6x=6Now, to isolate x, we must divide out the 6:6x=6 (6x divided by 6= x)x=1If 8x=2x+6, x=1
6x
-6x, -4x =
x^2 + 6x + 9 cannot be simplified further. If x^2 + 6x + 9 = 0 then we can solve for x. x^2 + 6x + 9 can be broken into a binomial: (x+3)(x+3), which then gives us x = -3.
3 and the solution is x = -5 and y = -3 When subtracting the equations remember that a - - is equal to a + So: - 6x - - 6x = 0 Also remember that a minus times a minus that the product is always a plus.
x2 - 6x - 27 = (x-9)(x+3)
x = 0,1
9x2+6x-8 = 0 (3x+4)(3x-2) = 0 Therefore: x = -4/3 or x = 2/3